2009
DOI: 10.1093/jac/dkp299
|View full text |Cite
|
Sign up to set email alerts
|

XF-73, a novel antistaphylococcal membrane-active agent with rapid bactericidal activity

Abstract: XF-73 exhibited rapid membrane-perturbing activity, which is likely to be responsible for inhibition of macromolecular synthesis and the death of staphylococci exposed to the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 10 publications
4
66
0
Order By: Relevance
“…In contrast, there was a significant increase in the MIC for three of the comparators against all the strains tested and two of four strains for vancomycin using the same conditions. XF-73 has a very rapid bactericidal activity (26,27) and acts on both dividing and nongrowing bacterial cells (28), and investigations suggest that it has a novel MOA (26,27). The results reported in this study confirm that such an antibacterial profile is likely to reduce the potential for the emergence of bacterial mutational resistance.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In contrast, there was a significant increase in the MIC for three of the comparators against all the strains tested and two of four strains for vancomycin using the same conditions. XF-73 has a very rapid bactericidal activity (26,27) and acts on both dividing and nongrowing bacterial cells (28), and investigations suggest that it has a novel MOA (26,27). The results reported in this study confirm that such an antibacterial profile is likely to reduce the potential for the emergence of bacterial mutational resistance.…”
Section: Discussionsupporting
confidence: 68%
“…As the proposed antibacterial MOA for daptomycin (16,30) is similar to that proposed for XF-73 (26,27), both of which appear to target the bacterial membrane, resulting in membrane depolarization and loss of intracellular components, it was also included in this study. In vitro reduced susceptibility to daptomycin in S. aureus NRS384 (USA300) emerged after only five repeat passages and remained stable after 10 serial passages in drug-free conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that these novel compounds can be used as lead compounds for the development of antimicrobial agents. The potent inhibition of macromolecule synthesis and rapid bactericidal activity of compounds 1 and 3 suggested that they, like daptomycin 18 and XF-73, 19 might damage bacterial membranes. Further experiments are required to gain more insight into the exact mechanism of action of these novel compounds.…”
Section: Discussionmentioning
confidence: 99%